PENGARUH PROGRAM KOPERASI, KEMAMPUAN SUMBERDAYA MANUSIA DAN PARTISIPASI ANGGOTA TERHADAP KEBERHASILAN KOPERASI SIMPAN PINJAM - Nur Khasanah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
The Cooperative, Micro, Small and Medium Enterprises Sector (CMSME) is a business sector that has proven to play an important role in overcoming the consequences and effects of teh economic crisis. The objective of this study was to determine the effects if cooperative programs, human resource capabilities and member participation on the success of Sharia savings and loan cooperatives BMT Usaha Gabungan Terpadu Sidogiri Pasuruan. The study conducted on cooperative members who minimum has been a member for 2 years.